PROBLEMS OF ASSESSING THE EFFECTIVENESS OF YOUTH POLICY IMPLEMENTATION - Khachak S. K. (Pedagogy, Psychology, Society, 2023)
The article discusses the problems of assessing the effectiveness of youth policy implementation. Optimization of youth policy, conceptual justification and development of technologies for a competently built trajectory of transforming the potential of young people into active social, political and economic activities to achieve the strategic goals of the state, the development of effective methods for assessing the results are the necessary conditions for the youth policy implementation at all levels of administration. Social projecting allows to obtain two types of results: the first is the quality of the produced project product; the second is an indicator of human qualities changes level in the project participant. The results of the research can be applied in the sphere of forecasting socio-political processes and designing youth policy programs in the region
Keywords: государственная молодежная политика; молодежь; youth; state youth policy; municipal youth policy; assessment of the implementation effectiveness; implementation process management; муниципальная молодежная политика; оценка эффективности реализации; управление процессом реализации